Niobium sintering process using design of experiment: Taguchi`s method - Rosinei, B. R.; Fernando, V.; Gilbert, S.; De O, Rafaela V.; Messias, B. S. [UNESP] (Trans Tech Publications, 2015)
In the last years it has been used statistical tools for industrial optimization processes, research and development, in order to minimize the amount of experiments and to establish the best relationships among representative variables. Obtaining the metallic materials route metallurgy powder, the sintering process is preponderant in the final properties of material. Several factors influence in the sintering process, such as: the medium particles size of powder, the final temperature, the isothermal time and other. To establish these factors for the sintering of a certain material requests a meticulous study. In this work the Taguchi's method of was used with head office orthogonal L9, for optimization sintering to niobium in high vacuum, being the porosity the variable response. The studied variables were the particles size of the niobium powder, the sintering temperature and the isothermal time, with levels: 25, 38 and 44 microns 1800, 1900 and 2000 °C, 0.5, 2 and 4 hours respectively. The porosity, the grain size and all features microstructure of the niobium sinterized were characterized by metallography analysis and Scanning Electronic Microscopy - SEM. Measurements the microhardeness (Vickers tests) and systems of digital processing and image analysis were realized.
Keywords: Design of Experiment; Metallography; Niobium; SEM; Sintering